2019
DOI: 10.20945/2359-3997000000152
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone therapy for women with low sexual desire: a position statement from the Brazilian Society of Endocrinology and Metabolism

Abstract: Objective: To summarize current evidence regarding testosterone treatment for women with low sexual desire. Materials and methods: The Female Endocrinology and Andrology Department of the Brazilian Society of Endocrinology and Metabolism invited nine experts to review the physiology of testosterone secretion and the use, misuse, and side effects of exogenous testosterone therapy in women, based on the available literature and guidelines and statements from international societies. Results: Low sexual desire is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
(106 reference statements)
0
6
0
2
Order By: Relevance
“…3,5 As doses estudadas na reposição de testosterona assemelham-se aos níveis fisiológicos de mulheres que ainda não passaram pela menopausa, o que se mostra um problema ao prescrever esse tratamento, uma vez que as apresentações comercializadas para a prescrição dessa terapia estão voltadas unicamente para os níveis séricos de testosterona masculinos. 6,8 Portanto, faz-se necessária a realização de estudos que avaliem os efeitos da testosteronaterapia em longo prazo, além da criação de apresentações adequadas aos níveis séricos deste hormônio na mulher. 6,7,8 CONCLUSÃO A reposição de testosterona nas mulheres cisgênero durante a menopausa mostra-se eficaz em curto prazo para disfunções sexuais na pós-menopausa.…”
Section: Métodosunclassified
“…3,5 As doses estudadas na reposição de testosterona assemelham-se aos níveis fisiológicos de mulheres que ainda não passaram pela menopausa, o que se mostra um problema ao prescrever esse tratamento, uma vez que as apresentações comercializadas para a prescrição dessa terapia estão voltadas unicamente para os níveis séricos de testosterona masculinos. 6,8 Portanto, faz-se necessária a realização de estudos que avaliem os efeitos da testosteronaterapia em longo prazo, além da criação de apresentações adequadas aos níveis séricos deste hormônio na mulher. 6,7,8 CONCLUSÃO A reposição de testosterona nas mulheres cisgênero durante a menopausa mostra-se eficaz em curto prazo para disfunções sexuais na pós-menopausa.…”
Section: Métodosunclassified
“…Women with HH have androgen deficiency. Although few studies have shown advantages with treatment (84), recent guidelines recommended against the routine use of DHEA and testosterone in women due to limited data concerning efficacy and safety (30,85,86). An intravaginal form of DHEA has been approved by the FDA to treat genitourinary syndrome of menopause, but this formulation is not available in Brazil (87).…”
Section: Sex Steroid Replacement Therapymentioning
confidence: 99%
“…An intravaginal form of DHEA has been approved by the FDA to treat genitourinary syndrome of menopause, but this formulation is not available in Brazil (87). Moreover, testosterone has been carefully suggested in the guidelines to treat selected women with hypoactive sexual desire disorder (85)(86)(87). In this clinical context, which might be present in women with hypopituitarism, a trial of low-dose testosterone therapy may be considered, which seems to be safe in the short term.…”
Section: Sex Steroid Replacement Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…(22,32) Premature ovarian insufficiency: A hormonal treatment approach Testosterone can be currently prescribed for women with POI diagnosed with hypoactive sexual desire disorder with no contraindication. (33,34) According to the literature, transdermal testosterone adhesive patches delivering 300 mcg/day are associated with an improvement in sexual function, but these are not commercially available in Brazil, being obtained through handling pharmacy. (35)(36)(37) Evidence suggest that testosterone levels should be used for three to six months with clinical and laboratory reassessment of serum testosterone levels (to verify whether the dose is not supraphysiological).…”
Section: How To Monitor and Follow Up Women With Poi?mentioning
confidence: 99%